A descrição da forma dos grãos de speckle na secagem de adesivo epóxi por expansão em Séries de Fourier - Mira, Anderson Rodrigo (2016)
The phenomenon known as dynamic laser speckle is used as a sensitive technique to monitor tinny movements in surfaces illuminated by a laser. The changes in the speckle pattern, in shape and clarity, are due to the movement of the scatterers of light and they are indirectly associated to the activity of a monitored material. In this context, this work aimed to present a direct way to quantify the movement by means of the shape monitoring of the speckle grains using the Fourier descriptors. It was used an epoxy glue during a drying process of 1024 seconds. The glue was illuminated by a HeNe laser and the images acquired by a CCD camera. The results showed that the Fourier descriptors follow the change in the grains along time, and that the first descriptors, particularly the first two, change more intensively their values than the last ones. The changes were more intense in the first moments of the drying process than when the glue was completely dry.